Prenatal diagnostic and management of megacystis microcolon intestinal hypoperistalsis syndrome: A report on a rare case in Cipto Mangunkusumo Hospital, Jakarta, Indonesia - Fita Maulina; Yuditiya Purwosunu (Majalah Obstetri dan Ginekologi, 2020)
Megacystis Microcolon Intestinal Hypoperistalsis Syndrome (MMIHS) is a rare and the most severe form of functional intestinal obstruction in the newborn. The characteristic features of this congenital and fatal disease are abdominal distension, absent or decreased bowel peristalsis. Abdominal distension is a consequence of the distended, unobstructed urinary bladder with or without hydro nephrosis. Some previous reports have revealed that the typical antenatal sonographic findings are as follows: a greatly distended bladder, bilateral hydro nephrosis, and a normal amount of amniotic fluid; however, the antenatal diagnosis of this syndrome is occasionally difficult.